PENGGUNAAN MEDIA SOSIAL SEBAGAI PROMOSI BISNIS DIGITAL TINJAUAN SYSTEMATIC LITERATURE REVIEW DENGAN MACHINE LEARNING - Deti Karmanita,; Jhon Veri, (Juremi: Jurnal Riset Ekonomi, 2024)
This research aims to examine the use of social media as a promotional tool in digital business through a Systematic Literature Review (SLR) approach supported by machine learning methods. Social media has become a major platform for marketing due to its ability to reach consumers widely and efficiently. This study identifies, evaluates, and interprets various research results related to the role of social media in improving marketing performance. The data used in this study comes from journal articles and proceedings published between 2020 and 2024, with a focus on social media and digital business. The SLR method is used to avoid subjective bias in the selection and assessment of literature. The results show that social media not only serves as an information channel, but also as an effective tool to build interactions with consumers, increase customer trust, and strengthen loyalty. Machine learning is used to analyze patterns and trends in the collected data, thus providing deeper insights into the effectiveness of social media in digital business promotion.